Uptake of ozone by allergenic pollen grains - Visez, Nicolas; Hamzé, Mona; Vandenbossche, Klervi; Occelli, Florent; de Nadaï, Patricia; Tobon, Yeny; Hájek, Tomáš; Choël, Marie (Environmental pollution (Barking, Essex, 2023)
Ozone exacerbates allergy symptoms to certain pollens. The molecular mechanisms by which ozone affects pollen grains (PGs) and allergies are not fully understood, especially as the effects of pollutants may vary depending on the type of pollen. In this work, pollens of 22 different taxa were exposed under laboratory conditions to ozone (100 ppb) to quantify the ozone uptake by the PGs. The ozone uptake was highly variable among the 22 taxa tested. The highest ozone uptake per PG was measured on Acer negundo PGs (2.5 ± 0.2 pg∙PG-1). On average, tree pollens captured significantly more ozone than herbaceous pollens (average values of 0.5 and 0.02 pg∙PG-1, respectively). No single parameter (such as the number of apertures, pollen season, pollen size, or lipid fraction) could predict a pollen's ability to take up ozone. Lipids seem to act as a barrier to ozone uptake and play a protective role for some taxa. After inhalation of PGs, pollen-transported ozone could be transferred to mucous membranes and exacerbate symptoms through oxidative stress and local inflammation. Although the amount of ozone transported is small in absolute terms, it is significant compared to the antioxidant capacity of nasal mucus at a microscale. This mechanism of pollen-induced oxidative stress could explain the aggravation of allergic symptoms during ozone pollution episodes.
Keywords: Hypersensitivity; Ozone; ozon; Atmospheric biochemistry; alergie; látky znečišťující životní prostředí; Allergy; Air pollution; Oxidative stress; alergeny; pyl; Allergens; Environmental Pollutants; Bioaerosol; Pollen